2021
DOI: 10.1038/s41467-021-21229-w
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional evolution of B and AGL6 MADS box genes in orchids

Abstract: We previously found that B and AGL6 proteins form L (OAP3-2/OAGL6-2/OPI) and SP (OAP3-1/OAGL6-1/OPI) complexes to determine lip/sepal/petal identities in orchids. Here, we show that the functional L’ (OAP3-1/OAGL6-2/OPI) and SP’ (OAP3-2/OAGL6-1/OPI) complexes likely exist and AP3/PI/AGL6 genes have acquired additional functions during evolution. We demonstrate that the presumed L’ complex changes the structure of the lower lateral sepals and helps the lips fit properly in the center of the flower. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
(69 reference statements)
1
35
0
Order By: Relevance
“…The former is specifically expressed and exclusively required for labellum formation and reported as L‐code mode in orchids. The latter is reported as the P‐code of perianth development to specify the sepal/petal previously (Hsu et al ., 2015a , 2021 , 2015b , 2015a , 2021 , 2015b ). Among these expanded clades, we originally found that one of the four gene copies in SEP clade, CsSEP4 , was ectopically expressed in the gynostemium of the wild‐type flower and expended to all floral organs of a gynostemium‐like perianth variant.…”
Section: Resultsmentioning
confidence: 99%
“…The former is specifically expressed and exclusively required for labellum formation and reported as L‐code mode in orchids. The latter is reported as the P‐code of perianth development to specify the sepal/petal previously (Hsu et al ., 2015a , 2021 , 2015b , 2015a , 2021 , 2015b ). Among these expanded clades, we originally found that one of the four gene copies in SEP clade, CsSEP4 , was ectopically expressed in the gynostemium of the wild‐type flower and expended to all floral organs of a gynostemium‐like perianth variant.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the R2R3-MYB, bHLH, and WD-Repeat proteins, including those that we have briefly highlighted in this study, are prime candidates given that they are key determinants of anthocyanin pigmentation intensity and also patterning in many flowers ( Davies et al, 2012 ; Wessinger and Rausher, 2012 ). However, MADS-box transcription factors should also be investigated as some are involved in establishing proper floral organ identity programs, photosynthesis, chlorophyll metabolism, and pigmentation in orchids ( Pan et al, 2014 ; Hsu et al, 2021 ). The integration of various omics approaches (e.g., large-scale transcriptomic, metabolomic, ionomics) is also anticipated to provide a holistic view of how structural genes, regulatory factors, and cellular constituents (e.g., pigments, metal ions, pH) interact and mediate the evolutionary color transitions between sexually deceptive systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we analyzed the relationships among CmAP3, CmUIF1, and CmPI, which belongs to the class B GLOBOSA/PISTILLATA subfamily of MADS-box TFs ( Fig. S11 ) and has been reported to interact with AP3 to determine the organ identity of petals and stamens [ 21 , 61 ]. The results showed that CmAP3 was not able to interact with CmUIF1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CYC2c and CYC2g determined the position and zygomorphy of ray florets [ 68 ]. CYC2d was shown to repress the growth of stamens and dorsal corolla lobes [ 61 , 62 ]. In general, research on the regulatory mechanism of CYC2 -like genes has focused mainly on protein–protein interactions [ 70 , 71 ], whereas the regulatory networks upstream of these genes are poorly understood.…”
Section: Discussionmentioning
confidence: 99%